Impact of introduction of Mini-Clinical Evaluation Exercise in formative assessment of undergraduate medical students in pediatrics - Buch, Pankaj M. (International Journal of Contemporary Pediatrics, 2019)
Background: Student’s assessment is a systemic process of determining the extent to which the student has achieved the desired competency. Mini–Clinical Evaluation Exercise (Mini-CEX) is an assessment tool applicable in broad range of settings. Very little data is available in Indian settings about Mini-CEX in undergraduate. This study has been undertaken to understand its role in formative assessment. Methods: In this interventional study 47 students and 7 faculty of pediatrics participated. Students were assessed for two encounters of Mini-CEX. Assessment was as per Mini-CEX rating form followed by feedback. Results: Mean score range for different competency of data gathering were 1.76 to 2.5 during first mini-CEX and 4.38 to 5.14 during second Mini-CEX. Difference was significant (Cohen’s d >0.8). More than 90% of students felt that Mini-CEX is better way to assess clinical skills and would like to be assessed by Mini-CEX. One to one interaction was most important advantage felt about Mini-CEX. Though nearly all faculties felt that Mini-CEX is a better way for assessment half of them disagree to continue using it in future due to time constraints. Conclusions: In this study we found Impact of Mini-CEX in formative assessment is significant to improve clinical competency at undergraduate level. Improvement in Mini-CEX scores in consecutive encounter signifies its role even as Teaching Learning tool. Need to consider issues about its feasibility for Undergraduate level in settings with limited staff strength.